Gallbladder Agenesis: A Case Report - Salazar, Michelle C. (Yale J Biol Med, 2018)
Gallbladder agenesis (GA) is an extremely rare congenital entity. The incidence is around 1 per 6500 live births. The majority of patients, estimated between 50 to 70 percent, remain asymptomatic while those who are symptomatic report symptoms mimicking biliary colic. Initial workup for suspected gallbladder pathology such as right upper quadrant ultrasound (US) can be misleading or inconclusive. Furthermore, advanced diagnostic studies such as hepatobiliary iminodiacetic acid (HIDA) scan and endoscopic retrograde cholangio-pancreatography (ERCP) may report non-visualization of the gallbladder and erroneously lead providers to a diagnosis of cystic duct obstruction rather than GA. Consequently, some GA patients are only finally diagnosed intraoperatively. Surgery can be risky in these patients because unnecessary dissection while looking for the non-existent gallbladder can result in injury of the biliary tree, hepatic vasculature, or small bowel. Therefore, clinicians should keep GA on their differential diagnosis list and imaging modalities such as magnetic resonance cholangiopancreatography (MRCP) should be obtained when other tests prove inconclusive. We report a 35-year-old female presenting with chronic symptoms consistent with biliary colic and an equivocal US reported as cholelithiasis. She underwent laparoscopy during which the absence of the gallbladder was noted. Postoperative MRCP confirmed the diagnosis of GA.